Optimalisasi Framework TIDD-EC dalam Implementasi Prompt Engineering pada Pengembangan Website Company Profile Menggunakan Platform Antigravity dengan Metode Agile - Nabilah Syahwalrani; Putri Fathonah; Wasilah Maulia; Dicky Pratama (JOURNAL SAINS STUDENT RESEARCH, 2026)
The rapid advancement of Generative AI technology has created new opportunities in website development, particularly through prompt engineering techniques that enable users to guide Large Language Models (LLMs) in generating structured and high-quality code. This study aims to optimize the TIDD-EC framework (Task Type, Instructions, Dos, Don'ts, Examples, and Context) in the implementation of Prompt Engineering for developing a company profile website using the Antigravity platform with the Agile methodology. The TIDD-EC framework is utilized to structure instructions given to AI, ensuring that the generated outputs are more precise, relevant, and efficient. This research adopts an iterative development approach based on the Agile methodology. The results indicate that the implementation of the TIDD-EC framework significantly improves the quality and accuracy of AI-generated outputs during the website development process, reduces development time, and produces a website that aligns with client specifications. This study contributes to the advancement of prompt engineering methodologies and AI-assisted web development.